Prediksi Tingkat Kemiskinan di Provinsi Aceh dengan Model AR - Munawar, Munawar; Hafnani, Hafnani (Universitas Bengkulu, 2015)
One indicator of the success of a government is the decreasing in the poverty rate. This paper aims to predict the percentage of poverty in the province of Aceh based on 9 years time series data, from 2005 up to 2013. The research method is autoregressive model . The data is secondary data obtained from Badan Pusat Statistik (BPS – Statistics Indonesia) of Aceh Province. The model obtained is . Based on the model The prediction of the level of poverty in Aceh for 2014 is 18.27 percent of the total population of Aceh. This prediction has an error value of 0.22 and 1.29 respectively to the percentage of the poverty level in Aceh in March and September 2014. When viewed by urban and rural, the model obtained is and respectively for urban and rural. While the predictive value of the poverty level in Aceh in 2014 for urban areas is 11.73 percent and in rural areas is 20.81 percent.